Analysis of oral and pulmonary mycoses in suspected subjects of pulmonary tuberculosis visiting Indian healthcare center - Shiral, Hema; Goel, Renu; Rangari, Priyadarshini; Rangari, Amit A. (International journal of health sciences, 2022)
Background: Fungal infection of the lungs caused by endemic, opportunist, or combined fungi is pulmonary mycosis comprising a wide range of fungal diseases commonly seen in debilitated or immunocompromised subjects. Aims: To identify the pulmonary mycoses occurrence in suspected subjects of pulmonary tuberculosis (TB) by identifying and isolating various fungi causing pulmonary mycoses. Methods: 400 samples were taken from 200 suspected subjects of pulmonary TB where acid-fast staining was done to identify AFB (acid-fast bacilli), KOH, and gram stain to assess fungal element presence followed by culture on SDA to study fungal morphology. Germ-tube test used for C. Albicans identification. Results: Pulmonary mycosis was seen in 58 study subjects where candida species were the most commonly isolated fungal organism seen in 51.72% (n=30) study subjects followed by Aspergillus Niger, which was isolated in 20.68% (n=12) study subjects from their sputum. Candida albicans were most common and were isolated in 7 males where 3 were in the age of 11-20 years and 4 in 31-40 years, whereas Candida species were isolated from 23 females where in 11-20, 41-50, and 51-60 years had 3 females each, 61-70 years range had 5 females, and 9 females were in the age of 71-80 years.